The Internet of Things-Based Work Equipment Lending System at PT Namasindo Plas - Andang Syafrudin; Afu Ichsan Pradana; Dwi Hartanti (Green Publisher Indonesia, 2026)
The borrowing of work tools plays an essential role in supporting production activities at PT Namasindo Plas. The current borrowing process is still carried out manually using logbooks and spreadsheets, which often leads to issues such as inaccurate records, inconsistencies in inventory data, and the risk of tool loss. This research aims to develop an Internet of Things (IoT)-based work tool borrowing system equipped with Radio Frequency Identification (RFID) technology to enable automatic identification of tools and users, as well as real-time recording of all borrowing activities. The system was developed using the Waterfall method, which includes requirement analysis, system design, device assembly, testing, and implementation. The system utilizes an RFID module, an ESP8266 microcontroller, and an online database to store and manage borrowing information. The test results show that the system successfully reads RFID tags, records borrowing and returning transactions automatically, and updates tool status in real time. The implementation of this system improves data accuracy, speeds up the borrowing process, and reduces the potential for tool loss, thereby enhancing the operational efficiency of the warehouse at PT Namasindo Plas.